(untitled) (Orinoquia, 2017)
Different types of neoplasia have been observed in different species of animals. Neoplams are divided by the tissue of origin and its degree of malignancy. They may be of epithelial, mesenchymal origin, of round cells and of pigment-producing cells. According to the degree of malignancy, they are classified as benign and malignant. Carnivores constitute an order belonging to the animal kingdom, within which are several families. Depending on the interaction they have with the environment and exposure to pollutants, viruses and stressful situations, some individuals from a different family may develop a neoplasia. In both felids and canids, we have found a higher incidence of epithelial neoplams involving the integumentary system. In pinnipeds, the system most affected is the reproductive tract. There are few reports of neoplasms in procyonidae and mustelids, which may suggest a greater genetic resistance to the presentation of neoplams, or to a lesser carcinogenic exposure. The main purpose of this article is to identify the neoplasias in wild species, since these serve as sentinels of the ecosystem and help to determine possible carcinogenic pollutants in the environment. Knowing the degree of similarity in the genesis and tumor progression in humans, in relation to the wild life generates opportunities of treatment and conservation. They can serve as effective sentinels for public health problems. In addition, it is important in favoring and strengthening mechanisms directed to the health and conservation of wild species, since they can be reduced considerably because of this type of diseases.